Potential roles of oxidative distress on neurodegeneration in Parkinson's disease with neuropsychiatric symptoms - Li, Dan-ning; Lian, Teng-hong; Zhang, Wei-Jiao; Zhang, Ya-nan; Guo, Peng; Guan, Hui-ying; Li, Jing-hui; He, Ming-yue; Zhang, Wen-jing; Zhang, Wei-jia; Luo, Dong-mei; Wang, Xiao-min; et al. (Frontiers in Aging Neuroscience, 2022)
Background Neuropsychiatric symptoms (NPSs) is one of non-motor symptoms in Parkinson's disease (PD), which seriously compromises the quality of life and prognosis of PD. This study focused on the correlations among NPSs, hydrogen peroxide (H2O2) and nitric oxide (NO), neuroinflammatory factors, and neuropathological proteins in cerebrospinal fluid (CSF) from PD patients, aiming to provide insights into the potential mechanisms and therapeutic target for PD-NPSs. Methods Totally 129 PD patients were enrolled and assessed by Neuropsychiatric Symptoms Inventory (NPI), and divided into PD-NPSs group (75 patients) and PD with no NPSs (PD-nNPSs) group (54 patients). The levels of H2O2, NO and hydroxyl radical (·OH), anti-oxidative enzyme, neuroinflammatory factors and neuropathological proteins in CSF from PD patients were measured. The levels of above variables were compared between PD-NPSs and PD-nNPSs groups, and the correlation analyses among the above variables were conducted. Results 1. The levels of hydrogen peroxide (H2O2) and nitric oxide (NO) in CSF from PD-NPSs group were significantly elevated compared with PD-nNPSs group（p=0.001）, and NPI score positively correlated with the levels of H2O2 and NO（r=0.283，P=0.001; r=0.231, P=0.008）. Reversely, total superoxide dismutase (tSOD) activity in CSF from PD-NPSs group was significantly reduced compared with PD-nNPSs group（p=0.011）, and negatively correlated with NPI score（r=-0.185, p=0.036）. 2. Tumor necrosis factor (TNF)-α level in CSF from PD-NPSs group was significantly decreased compared with PD-nNPSs group（p=0.002）, and negatively correlated with NPI score（r=-0.211, p=0.016）. 3. Total tau (T-tau) level in CSF from PD-NPSs group was significantly higher than PD-nNPSs group（p=0.014）, and positively correlated with NPI score（r=0.167, p=0.060）. 4. The levels of H2O2 and NO positively correlated with T-tau level in CSF from PD-NPSs group（r=0.183, p=0.039;r=0.251,P=0.004）, and the levels of TNF-α and T-tau negatively correlated（r=-0.163, p=0.067） Conclusions Oxidative distress characterized by elevation of H2O2 and NO levels may closely correlate with the neurodegeneration in brain regions related to PD-NPSs. Thus, therapeutic antioxidants may become an important target for PD-NPSs therapy.